Template Synthesis of Transition Metal Complexes with Octaamide Macrocyclic Ligand† - SANGEETHA, J.E.; MEENALOCHANI, S.; RADHA, K.; SELVAN, A.; CHELLAPPA, D. (Asian Journal of Chemistry, 2010)
The ‘one-pot’ template synthesis of metal complexes with a new [2+2] macrocycle bearing four oxamide units is reported. The metal complexes MLX2, where M = Cu(II), Co(II), Ni(II), Mn(II) and Zn(II), L = 1,4,7,10,13,16,19,22- octaazacyclotetracosane-2,3,8,9,14,15,20,21-octaones and X = Cl–/ OAc– have been characterized by elemental analysis, molar conductance, magnetic susceptibility measurements, electronic, IR and EPR spectral studies. On the basis of these studies Cu(II) complex has been assigned tetragonal geometry while other complexes are assigned octahedral geometry and are found to be high spin.